O nó entre a terra e o mar: Caiçaras, resistência e participação social - Sardinha, Thaiz Marina de Medeiros (2023)
Traditional communities are defined as culturally differentiated groups that recognize themselves as such and have as a striking characteristic their interaction with the territory. The Vale do Ribeira region, located in the south of the state of São Paulo, concentrates a large number of traditional communities, in addition to being part of one of the most important socio-environmental corridors in the country. It is also a region with an extensive area of preserved Atlantic Forest, with a strong presence of Nature Conservation Units. The present study aimed to rescue and highlight the peculiar relationships between caiçara communities in Vale do Ribeira and how their relationship with natural resources and conflicts exist between these communities, nature conservation units and development projects. In this sense, it is necessary to understand the configuration of space in Vale do Ribeira in light of the multiple forms of use and appropriation of natural and territorial resources. Militant research constituted the guideline chosen for the analysis of the processes, to verify the territorialities that emerge from traditional peoples and communities with regard to socio-environmental conflicts. Field research was carried out with the caiçara communities of Iguape (SP), located in the Mosaic of Conservation Units of Juréia – Caiçaras do Rio Verde and Praia da Juréia – Barra do Ribeira, in their peculiar relationship between land and the sea, between agricultural activities and fishing activities. Bringing light to the issue of the history of resistance in the struggle for territory, which marks the daily lives of caiçara communities. When making these choices, territorial uses and appropriations in the Ribeira Valley were listed, which social subjects are involved in socio-environmental conflicts, which interests and strategies, in the face of rights violations, that permeate these conflicts, organized through a framework typology of these conflicts and the actions of resistance and participation that have been built and rebuilt by traditional caiçara communities. From the perspective of presenting that from the struggle for land and territory, they highlight a range of struggles that through the use and management of natural resources, resistant traditional territorialities emerge